8.5k views
12 votes
5y + 3 = 8y − 5 + 2y

User Guy Dafny
by
4.4k points

2 Answers

11 votes

Answer

= 8/5 hope this is fine

User Mawalker
by
5.2k points
1 vote

Answer:


\fbox{y = 8/5 }

Step-by-step explanation:

[to solve for y, first use the properties of equality to simplify the equation]

5y + 3 = 8y − 5 + 2y

5y + 3 = (8y + 2y) – 5

[regroup the like terms of y together: commutative property of equality ; adding in a different order will still give you the same result]

5y + 3 = 10y – 5

[combine like terms]

5y + 3 = 10y – 5


\: \: \: \: \: \: -3 \: \: \: \: \: \: \: \: \: \: \: -3

[subtract 3 from both sides in order to eliminate the constant term on the left side: subtraction property of equality]

5y = 10y – 8

–10y –10y

[subtract 10 from both sides in order to eliminate the variable term: subtraction property of equality]

-5y = -8

÷(-5) ÷(-5)

[divide both sides by -5 to cancel out the coefficient of y: division property of equality]

y = 8/5

User Kauedg
by
4.9k points